Changes in loaded countermovement jumps during precompetition and competition training mesocycles in elite rowers - Everett, K. L.; Chapman, D. W.; Mitchell, J. A.; Ball, N. (The Journal of Strength and Conditioning Research, 2022)
To assess changes in velocity, displacement, and power as an indicator of neuromuscular fatigue (NMF) within and between precompetition and competition mesocycles in elite male rowers using loaded countermovement jumps (CMJs). Twenty highly trained rowers completed regular training (on-water rowing, rowing ergometer, and resistance training sessions) in 2 consecutive mesocycles. Athletes completed a single set of 6 loaded (20 kg) CMJs in the first and final week of each mesocycle. Countermovement jumps were assessed for jump height (JH), eccentric displacement, mean velocity (MV), eccentric MV (EMV), and mean power. Changes between time points were reported as Cohen's d effect sizes (95% confidence interval [CI]). The magnitude of the differences was also considered based on their relative strength levels using a linear mixed model. Within the precompetition mesocycle, trivial-to-small reductions for all variables (0.5-4.1%) were observed. During the competition mesocycle, trivial-to-small increases were shown for EMV (1.4%) and eccentric displacement (2.0%) with no change in JH and small reductions in MV (0.5%) and mean power (2.8%). No differences between the precompetition and competition mesocycles were shown. Only mean power showed a significant reduction in weaker athletes (3.2%) compared with stronger athletes (2.3%). Training completed during a precompetition and competitive mesocycle did not result in significant decreases in athlete's loaded CMJ performance, indicating that NMF was minimized. Alternatively, use of a loaded CMJ may not be sensitive enough to observe NMF in elite rowers during the mesocycle immediately leading into and during a competition mesocycle.